“Efecto antibacteriano in vitro del extracto etanólico del fruto Capsicum pubescens (rocoto) sobre Streptococcus mutans ATCC 25175” - Díaz Gamarra, Jhon Silver (2020)
The purpose of this research is to determine the existence of the antibacterial "In vitro" effect of the ethanolic extract of Capsicum pubescens on the Streptococcus mutans strain ATCC 25175. First, the ethanolic extract was gotten through the Leaching technique to the Capsicum pubescens "Rocoto" fruit, getting solutions of 25%, 50% and 75%. Then, to determine the antibacterial effect, the bacterial susceptibility was evaluated by the Kirby and Bauer method, measuring the diameter of the inhibition halo. Likewise, the Minimum Bactericidal Concentration (MBC) was determined through the extended method in Petri dishes by counting Colony Forming Units (CFU). In both methods, concentrations of 25, 50, and 75% were used, plus a control drug (2% Chlorhexidine Gluconate). The average of the halos obtained by the Kirby and Bauer method, the concentrations 25%, 50%, 75%, and the positive control of 2% Chlorhexidine Gluconate were 9.62mm, 10.31mm, 11.54mm and 22mm, respectively. The counting of Colony Forming Units (CFU) showed zero at all concentrations, including the control drug. It is concluded according to the obtained data, that there is an antibacterial effect "In vitro" of the ethanolic extract of the Capsicum pubescens (Rocoto) on the Streptococcus mutans strain ATCC 25175.